(untitled) (Asian Journal of Medical and Biological Research, 2024)
Cross-contamination of food contact surfaces can impose crucial barriers to food safety. Ready-to-eat (RTE) food items’ have the possibility of contamination during handling and serving from the terminal contact surfaces like hands, serving plates and tables, spoons, knives, and glasses. Considering these, this study was aimed to investigate the microbial load of these contact surfaces. Swab samples were collected from four crucial RTE foods contact surfaces for instance food handlers’ hands (HHS), plates (PS), tables (TbS), and spoons (SS) surfaces of twenty randomly selected local restaurants. To quantify the microbial load of these surfaces, total viable count (TVC) count was assessed using nutrient agar (NA), and total coliform (TC) count and fecal Escherichia coli (E. coli) were identified based on colony characteristics on chromocult coliform agar (CCA) media using standard methodologies described in previous studies. E. coli colonies from all contact surfaces and bacterial colonies isolated from HHS samples were confirmed by biochemical tests. Substantial number of bacterial presence was observed in all the samples, where TbS (1.93×105 CFU/cm2) and HHS (6.77×104 CFU/cm2) and SS (2.80×102 CFU/cm2) and HHS (2.88×102 CFU/cm2) had the highest TVC and TC count respectively. 65% of all samples were found to be contaminated with fecal E. coli while HHS samples harbored major foodborne pathogens like Salmonella, Shigella, Klebsiella spp., and Bacillus cereus. The study indicates poor microbial quality of these food contact surfaces which could implicate cross-contamination of the food items and incidences of foodborne illness among the consumers of these restaurants. These scenarios urge further studies on routes of these microbial contamination and limiting ways to enhance food safety in these restaurants. Asian J. Med. Biol. Res. 2024, 10(1), 71-79